2016
DOI: 10.3892/or.2016.5289
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 promotes cisplatin-resistance of non-small cell lung cancer in a CYP1B1-dependent manner

Abstract: Chemoresistance is the main cause of treatment failure and high mortality in advanced lung cancer. Cisplatin, an important chemotherapeutic agent for lung cancer, has been observed to show enormously reduced chemotherapeutic efficacy owing to the development of chemoresistance. CXCR4, a stromal-derived-factor-1 specific chemokine receptor, is highly expressed in non-small cell lung cancer (NSCLC) tissues and participates in cancer progression by regulating cell growth, apoptosis or invasion. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…pMSC downregulates CXCL12 in LPS-induced ALI. in our previous studies it was demonstrated that the activation of the cXcl12/cXcr4 axis played an important role in the metastasis and drug resistance in lung cancer (26)(27)(28). Moreover, cXcl12 could serve as pro-inflammatory chemokines as was reported in some previous studies (17,18).…”
Section: Effect Of Pmscs On Balf Inflammatory Cells and Proteinsmentioning
confidence: 55%
“…pMSC downregulates CXCL12 in LPS-induced ALI. in our previous studies it was demonstrated that the activation of the cXcl12/cXcr4 axis played an important role in the metastasis and drug resistance in lung cancer (26)(27)(28). Moreover, cXcl12 could serve as pro-inflammatory chemokines as was reported in some previous studies (17,18).…”
Section: Effect Of Pmscs On Balf Inflammatory Cells and Proteinsmentioning
confidence: 55%
“…It has been shown that CXCR4 is increased by 2–15 times in ovarian cancer cells compared to normal ovarian cells at the mRNA level [ 15 , 16 ]. Some studies have found that SDF1 and CXCR4 are highly expressed in cholangiocarcinoma [ 17 ], breast cancer [ 18 ], non-small cell lung cancer [ 19 , 20 ], cervical cancer [ 21 , 22 ], liver cancer Huh7 cells [ 23 ] and melanoma cells [ 24 ]. Hypoxia also induces the expression of SDF1/CXCR4 in tumor cells [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In platinum-resistant cells, several molecular mechanisms, such as increased DNA-repair capacity or the alteration of DNA-damage associated pathways, result in apoptosis inhibition and cell survival, following cisplatin treatment [ 17 ]. In platinum-resistant A2780cis cells, we observed a 5-FdU-ECyd mediated activation of cytochrome p450 drug metabolization pathways, which are known to confer chemo-resistance [ 35 ]. Interestingly, although these pathways were activated, the antitumor effect of 5-FdU-ECyd was not impaired at all in these cells.…”
Section: Discussionmentioning
confidence: 99%